Dort, Doleantie and Church Order - Faber, Ryan (2020)
This article attends to the relationship between minor and major assemblies as prescribed by the foundational principles of Reformed church polity proposed by Mary-Anne Plaatjies-Van Huffel. It reviews the limited autonomy of local congregations and the authority of broader assemblies in the Church Order of Dordrecht (1618/19), the touchstone of Dutch Reformed church polity. It considers the challenge to historic Reformed church polity posed by the ecclesiology of the Doleantie, a secession from the Nederlandse Hervormde Kerk (NHK) in 1886 under the leadership of Abraham Kuyper. Finally, it evaluates a contemporary church order (of the United Reformed Churches in North America), that explicitly codifies Doleantie ecclesiology. The church order fails to embody the principles of Reformed church polity set forth by Plaatjies-Van Huffel. This article concludes that it cannot be considered a Reformed church order.